Comparative Test of Reconstruction with the Modified Arthrodesis Metallic and Cement (MAMC) Technique and the Juvara Technique in Resisting Axial Compression After Distal Femur Resection - Septiandani, Randy Rakhmat; Primadika Rubiansyah; Iche Andriyani Liberty (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2024)
Background: Limb salvage surgery (LSS) is a crucial treatment for malignancies, which mostly affects the distal femur and proximal tibia. LSS encompasses biological and non-biological reconstructions, including megaprosthesis. However, limited access to megaprosthesis in developing countries has led to alternative methods like arthrodesis such as modified arthrodesis with metal and cement (MAMC). LSS may lead to complications, requiring careful technique and implant selection but none of them conduct research about mechanical test. This research was comparing the effectiveness of techniques like MAMC with Juvara, in mechanical axial loading perspective. Methods: In this true experimental study, conducted at the Metallurgy Laboratory of the Faculty of Engineering, Universitas Sriwijaya, femur and tibia bones from cattle were used. Five samples of each variable were used based on the purposive sampling method. The research focused on variables like deformity angle and yield point which assessed using X ray. Bone constructs underwent various fixation techniques, including MAMC and Juvara. Testing involved axial pressure on the femur head using a mechanical press machine. Statistical analysis compared implant angulation after compression between Juvara and MAMC techniques under 30 kg and 60 kg loads, ultimately measuring the yield point. Results: All five samples from each group, subjected to both 30kg and 60kg pressure, exhibited no discernible changes. The average yield point for the MAMC group was notably 160KgF higher than Juvara, with respective means of 296 and 126kgF (p>0.05). Further analysis employing an Independent T-test confirmed a significant disparity between the MAMC and Juvara techniques concerning the yield point with a p-value of <0.001. Conclusion: Both the MAMC and Juvara techniques in this study effectively supported 30 and 60-kilogram loads, demonstrating their suitability for full weight-bearing compression, with MAMC exhibiting significantly greater compression resistance compared to Juvara (p = 0.001).